The importance of the doctor-patient relationship in adherence to HIV/AIDS treatment: a case report - Garcia,Rosa (2005)
In this case report, which includes a statement related by the patient himself, the authors also discuss the importance of a good doctor-patient relationship in treating HIV patients and in assuring the patient's adherence to his treatment. Related issues, such as the importance of treating psychiatric comorbidities, of preserving the patient's hope and motivation, and of giving him an adequate amount of information regarding the disease and its treatment, are also discussed.